Burma 1942 : memories of a retreat : the diary of Ralph Tanner, 2nd Battalion the King's Own Yorkshire Light Infantry /: memories of a retreat : the diary of Ralph Tanner, 2nd Battalion the King's Own Yorkshire Light Infantry. (2011) - Unknown
No abstract available